ANALYSIS RENDEZVOUS-BASED TECHNIQUES RELATE TO POWER CONSERVATION - Agus Waryanto; Antonius Juniadhi Soekendar; Ely Andra Widharta; Greget Widhiati; Irdha Yunianto (University of Science and Computer Technology, 2022)
Power conservation is a vibrant area of research on wireless sensor networks. Several research papers have shown that using mobile sync in the sensor field, which collects data from sensor nodes via single or multi-hop communication, can save significant energy. However, sinks move slowly, which increases sensor network delays, especially in delay-sensitive applications. To address this issue, various rendezvous-based techniques are described in which a subset of sensor nodes are selected from the field as rendezvous points (RPs). The remaining nodes transfer the captured data to the next RP, where the data is buffered. The RP is then used to build a path for the mobile sink to tour and collect the buffered data. This article describes various rendezvous-based techniques and analyzes their strengths and weaknesses in terms of energy savings.